Exercise Speed, Agility and Quickness (SAQ) To Improve Physical Fitness - Nur Subekti; Agam Akhmad Syaukani; Muhad Fatoni; Subroto Subroto; Amar Abdullah Dani Arni Raihan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the speed, agility and quickness (SAQ) exercise in improving physical fitness. The sample of this study was a student of  a male in the Study Program of Sports Education Teacher Training and Education Faculty Universitas  Muhammadiyah  Surakarta peers of 30 people, to determine the sample using purposive sampling. This research method uses quasi-experimental research. Data analysis techniques using a constellation of one group pretest_posttest design. Data analysis techniques used in this study are using descriptive analysis and inferential analysis, descriptive analysis is used to describe the results of this research while inferential analysis using paired test samples at a significant level ?= 0.05 analysis used with the help of SPSS version 20.0. The results of this study showed that there is a significant influence of exercise speed, agility, and quickness (SAQ) to improve physical fitness in students of sports education FKIP Muhammadiyah University of Surakarta. Based on these findings, it can be assumed that SAQ training is an effective exercise to improve physical fitness. However, further research is needed to pay attention to other exercise methods that are associated with improving physical condition.